Establishment and Affirmation of Village Boundaries in Rancabali District, Bandung Regency Based on Ministerial Regulation No. 45 of 2016 with the Principle of Contradictoire Delimitatie - Sitorus, Hanny Wahyuningtiyas; Rohman, Arif; Yudanegara, Rizky Ahmad; Ramos, Ferdian (Journal of Science and Applicative Technology, 2024)
The boundary village is a parapet government administration of the region inter-villages which is a series of coordinates to which points are on the surface of the earth. This study examines the application of the Minister of Home Affairs Regulation Number 45 of 2016 concerning the determination and affirmation of village boundaries in Rancabali Sub-district, Bandung District, West Java Province, Indonesia. The Rancabali sub-district consists of five villages whose boundaries must be affirmed and defined. According to the Minister of Home Affairs Regulation Number 45 of 2016 in the determination and affirmation of village boundaries, it is defined as administrative boundaries inter-villages that are juridical. This study aims to determine and confirm village boundaries based on the methodology contained in Minister of Home Affairs Regulations number 45 of 2016 by producing the village's administrative boundaries from the results of cartometric technical agreements. The data of this study were sourced from village boundary data in a participatory manner by villages in Rancabali Sub District using cartometrics. Because the Minister of Home Affairs Regulation Number 45 of 2016 stipulates that the determination and affirmation of regional boundaries are carried out cartometrically so that the application of this method needs to be carried out on the determination of village boundaries. The results of this research resulted in technical agreements and maps of village/kelurahan administrative boundaries in Rancabali District. In the technical agreement activities carried out, it was possible to identify the boundaries between villages/kelurahan in Sukaresmi Village, the maps of Indragiri Village and Cipelah Village resulted in an agreement. Patengan Village and Alamenda Village still have areas where they disagree.